Faktor Yang Mempengaruhi Peningkatan Pembiayaan Bermasalah Pada Bank Syariah Indonesia Cabang Kudus Masa Pandemi Covid-19 - Viviani, Vinda; Aini, Muslikhatul; Hana, Kharis Fadlullah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Islamic banking in Indonesia was able to survive in the midst of the onslaught of the covid-19 pandemic that damaged the world's economic order, this can be seen from the average NPF value of Islamic banking in Indonesia which shows that it is still in the healthy category.This study aims to analysis the factors that influence the number of non-performing financing in Central Java is relatively high. This study uses a descriptive qualitative research method with a social phenomenology approach.Data collection was obtained from interviews with employee and customer informants of Bank Syariah Indonesia.This study show that the increase in non-performing financing is caused by the effects of social policies issued by the government during a pandemic that makes unemployment in Indonesia increase, business actors (SMEs) experience bankruptcy due to decreased income, which ultimately has an impact on financing defaults.